2012
DOI: 10.3109/08037051.2012.645335
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width in patients with prehypertension and hypertension

Abstract: RDW is higher in prehypertensive and hypertensive patients compared with healthy controls independently of age, inflammatory status and anemia. Higher RDW values are strongly correlated with higher systolic and diastolic blood pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 22 publications
8
86
0
3
Order By: Relevance
“…Besides, the activity of inflammatory bowel disease (22) as well as pulmonary functions (23) has also been reported to be associated with RDW values (24). RDW has been recently determined to be associated with hypertension and it was an indicator of poor prognosis in heart failure and acute myocardial infarction (10,25,26). Although the mechanism of the relationship between hypertension and RDW was not clearly understood, increased inflammation was the most reasonable theory (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the activity of inflammatory bowel disease (22) as well as pulmonary functions (23) has also been reported to be associated with RDW values (24). RDW has been recently determined to be associated with hypertension and it was an indicator of poor prognosis in heart failure and acute myocardial infarction (10,25,26). Although the mechanism of the relationship between hypertension and RDW was not clearly understood, increased inflammation was the most reasonable theory (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been shown that RDW was higher in prehypertension. Prehypertension was described as slightly elevated blood pressure which would likely turn into high blood pressure (hypertension) in non-pregnant people if lifestyle changes like eating healthier and starting to exercise were not done (10). Furthermore, the association between RDW values and non-cardiac and cardiac mortality in patients with cardiovascular and thrombotic disorders, diabetic ketoacidosis, acute and chronic heart failure, coronary artery disease, and stroke has been investigated (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier studies have reported the relationship between RDW and hypertension. Tanindi et al demonstrated that RDW is higher in prehypertensive and hypertensive patients than in healthy controls, and that RDW values have a strong relationship with SBP and DBP (20) . However, that study did not include an isolated systolic hypertension group.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found that it is correlated strongly with heightened systolic and diastolic blood pressure and is a poor prognostic indicator in cardiovascular disorders. [4,5,11] Ozcan et al have attributed the rise of RDW in hypertensive disorders to the increased inflammatory response. [12] By impairment of iron metabolism and disturbance in erythropoiesis, it could also result in the release of excess of reticulocytes and disruption in erythrocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has shown that increased levels are also seen in hypertension and other cardiovascular disorders. [4,5] It is also associated with diabetic ketoacidosis, thrombotic disorders, malignancies and hepatorenal diseases. [6,7,8] However, there is limited data on the usefulness of RDW in pregnant population and especially the hypertensive disorders of pregnancy.…”
Section: Introductionmentioning
confidence: 99%